2021
DOI: 10.1136/bmjopen-2021-049039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moxibustion on reproduction and metabolism of polycystic ovary syndrome: a protocol for meta-analysis and systematic review

Abstract: IntroductionPolycystic ovary syndrome (PCOS) is one of the most common endocrinopathy in women of reproductive age. Recently, moxibustion, as a complementary and alternative therapy, has been commonly used in assisted reproduction and improvement of metabolic abnormalities in patients with PCOS. Currently, intervention efficacy of the use of moxibustion in PCOS treatment still remains controversial due to lack of high-quality evidence. Consequently, this study protocol was designed to objectively review and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Desde la perspectiva de Li Y et al (17) y Lima et al existen resultados satisfactorios luego de las 5 sesiones del uso de la auriculoterapia, la cual se basa en la estimulación de puntos específicos de pabellón auricular y la oreja, con el objetivo de favorecer el equilibrio de las funciones corporales, la misma que es efectiva para el alivio del dolor, reducción del peso, la dismenorrea, cefalea y la ansiedad que es producida por el Síndrome de Ovario Poliquístico. En contraste con las investigaciones de Xu et al (27) y Lamba et al (32) la eficacia del uso de la moxibustión en mujeres en edad reproductiva ha mejorado las anomalías metabólicas y es beneficioso para mejorar la circulación sanguínea pélvica local, acelerando la absorción de medicamentos utilizados para la inducción a la ovulación y con ello promover la fertilidad. Sin embargo, según Feng et al (26) además del uso de la moxibustión y la acupuntura existen otras terapias como el enema de medicina china, la intervención psicológica y la estimulación eléctrica, las cuales son poco comunes y con baja evidencia científica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Desde la perspectiva de Li Y et al (17) y Lima et al existen resultados satisfactorios luego de las 5 sesiones del uso de la auriculoterapia, la cual se basa en la estimulación de puntos específicos de pabellón auricular y la oreja, con el objetivo de favorecer el equilibrio de las funciones corporales, la misma que es efectiva para el alivio del dolor, reducción del peso, la dismenorrea, cefalea y la ansiedad que es producida por el Síndrome de Ovario Poliquístico. En contraste con las investigaciones de Xu et al (27) y Lamba et al (32) la eficacia del uso de la moxibustión en mujeres en edad reproductiva ha mejorado las anomalías metabólicas y es beneficioso para mejorar la circulación sanguínea pélvica local, acelerando la absorción de medicamentos utilizados para la inducción a la ovulación y con ello promover la fertilidad. Sin embargo, según Feng et al (26) además del uso de la moxibustión y la acupuntura existen otras terapias como el enema de medicina china, la intervención psicológica y la estimulación eléctrica, las cuales son poco comunes y con baja evidencia científica.…”
Section: Discussionunclassified
“…Xu K et al (27) / 2021/ Scopus Proporcionar referencias para el tratamiento clínico del síndrome de ovario poliquístico.…”
unclassified
“…According to TCM, deficiency of kidney yang, deficiency of cold in the cellular veins and stasis blocking the thoroughfare and conception vessels are important etiological mechanisms of infertility, and moxibustion is widely used in the improvement of assisted reproduction and metabolic abnormalities in infertile patients with PCOS, because of its effects on warming the menstrual channels and dispersing cold, reinforcing yang and prostration, eliminating stasis and resolving masses, as well as preventing disease and health care. [75] Yu et al [76] found in an RCT that Chinese medicine combined with moxibustion at points BL23, DU2, DU4 and other acupoints could effectively regulate the level of sexual hormones, improve ovarian hemodynamics, increase OR, and thus improve PR (OR: 84.62% vs. 64.71%, PR: 48.8% vs. 23.53%, P < 0.05). Similar to moxibustion, warm acupuncture and moxibustion is a treatment in which moxa wool is twisted around the needle handle and ignited during needle retention, and the needle body transmits heat into the acupoint, which has the effect of warming the meridians and activating qi and blood.…”
Section: Moxibustion and Warmmentioning
confidence: 99%
“…In contrast, moxibustion therapy, an usual treatment of PCOS in traditional Chinese medicine, achieves therapeutic effects through warm stimulation and drug stimulation of body surface acupoints. It is characterized by its non-invasive nature, minimal adverse effects, simplicity of operation, and effectiveness ( Xu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%